2012
DOI: 10.1075/lab.2.3.03dek
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in native language attainment and their implications for research on second language acquisition

Abstract: Ewa Dąbrowska's article points to a much-neglected phenomenon indeed: variation in native language (L1) morphosyntax that is not sociolinguistic in nature, but which suggests competence differences that result from slightly different ways of solving the problem of inferring L1 grammar, in spite of learning mechanisms and input both being largely the same as for other learners of that same L1.In my comments I would like to focus on what this means for second language acquisition (SLA), and in particular for res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Commenting on the implications of the existence of individual differences in native speakers’ grammatical knowledge for work on second language acquisition (SLA), DeKeyser (, p. 260) suggested that researchers interested in age effects should “avoid structures for which quite a bit of variability [in L1 speakers] has been documented; otherwise it is a foregone conclusion that the ranges of L1 and L2 variation are going to overlap.” However, this recommendation seems unwarranted. First, overlap between L1 and L2 ranges for such structures is not a foregone conclusion: If a structure is difficult for native speakers, we could reasonably expect it to be even more difficult, and perhaps unlearnable, for adult L2 learners.…”
Section: Introductionmentioning
confidence: 99%
“…Commenting on the implications of the existence of individual differences in native speakers’ grammatical knowledge for work on second language acquisition (SLA), DeKeyser (, p. 260) suggested that researchers interested in age effects should “avoid structures for which quite a bit of variability [in L1 speakers] has been documented; otherwise it is a foregone conclusion that the ranges of L1 and L2 variation are going to overlap.” However, this recommendation seems unwarranted. First, overlap between L1 and L2 ranges for such structures is not a foregone conclusion: If a structure is difficult for native speakers, we could reasonably expect it to be even more difficult, and perhaps unlearnable, for adult L2 learners.…”
Section: Introductionmentioning
confidence: 99%